Seren Taun Tradition and Indigenous Food Security in the Kasepuhan Cisitu Community, Indonesia - Yeni Nuryani; Dwi Sulisworo; Ani Susanti (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
This study examines the role of the Seren Taun traditional ceremony and indigenous customs in maintaining food security among the Kasepuhan Cisitu Indigenous Community in Lebak Regency, Banten, Indonesia. Using a descriptive qualitative approach, the research explores how local wisdom, traditional agricultural practices, and communal values contribute to sustainable food resilience. The findings reveal that the Seren Taun ceremony is not merely a cultural celebration but also a social mechanism that reinforces agricultural sustainability, food storage systems, intergenerational knowledge transmission, and collective responsibility toward food sovereignty. The existence of leuit (traditional rice barns) functions as a symbol and instrument of long-term food security, enabling indigenous households to preserve rice stocks for years without dependence on external markets. Furthermore, the study highlights the integration of cultural values, environmental conservation, and community cooperation in strengthening local resilience against food crises. Government support through irrigation infrastructure is also identified as an important factor in sustaining indigenous agricultural productivity. This study demonstrates that indigenous knowledge systems can provide valuable insights for sustainable food security policies in contemporary society.